Medallion depicts a bird (likely a peacock) with its head bent downwards - Temples of India Project Team (Jio Institute, 2024)
Tablet-like plaques are placed on the adhisthana (facing east). These plaques depict various types of flora and fauna as well as hybrid creatures like kinnara, vyala, and makara. The plaques are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The central artwork of the plaque is in the form of a circular medallion surrounded by a foliage motif. In this medallion, a bird (likely a peacock) with its head bent downwards is integrated with a creeper motif. The rest of the plaque is covered with ardha padma (half lotus) and kalpa lata (creeper) motifs.